Task Clarity, Work Motivation, and Employee Performance: Evidence from the Mediating Role of Work Stress - Maria Anastasia; Jumriaty Jusman (Jurnal Ilmu Manajemen, 2026)
This study aims to examine the effects of task clarity and work motivation on employee performance, with work stress serving as a mediating variable, using the perspective of the Job Demands–Resources (JD-R) Theory. The research adopts a quantitative explanatory design and involves all 31 employees of the Martapura City Subdistrict Office as the research sample, applying a saturated sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that task clarity has a significant effect on work stress but does not directly influence employee performance. Work motivation is found to have a positive and significant effect on both work stress and employee performance. Furthermore, work stress has a positive and significant effect on employee performance, indicating that manageable levels of stress may function as a challenge stressor that enhances performance. The indirect effect analysis reveals that work stress significantly mediates the relationship between task clarity and employee performance, while its mediating role in the relationship between work motivation and performance is marginally significant. These findings suggest that employee performance is not solely determined by structural and motivational factors but is strongly influenced by psychological mechanisms, particularly work stress. From a theoretical perspective, this study strengthens the JD-R Theory by demonstrating that job and personal resources often affect performance indirectly through stress-related processes. Practically, the results highlight the importance of managing work stress optimally when improving task clarity and work motivation, especially in public sector organizations.